A Delay‐Aware Congestion Control Protocol for Wireless Sensor Networks. Issue 3 (1st May 2017) - Pei, Tingrui; Lei, Fangqing; Li, Zhetao; Zhu, Gengming; Peng, Xin; Choi, Youngjune; Sekiya, Hiroo
Abstract : In wireless sensor networks, congestion leads to buffer overflowing, and increases delay. The traditional solutions use rate adjustment to mitigate congestion, thus increasing the delay. A Delay‐aware congestion control protocol (DACC) was presented to mitigate congestion and decrease delay. In order to improve the accuracy of the existing congestion detection model which is based on the buffer occupancy of a single node, DACC presents a new model considering both the real‐time buffer occupancy and the average transmission time of packets. DACC uses the untapped bits in the IEEE 802.11 Distributed coordination function (DCF) frames header to carry congestion information. During the congestion alleviation period, DACC presents a channel occupancy mechanism which is based on the real‐time buffer occupancy for the purpose of decreasing delay and preventing packet loss. Simulation results indicate that in terms of delay, packet delivery ratio, collision and buffer load, DACC has comparative advantages than those of 802.11 DCF, Priority‐based congestion control protocol (PCCP) and Decoupling congestion control and fairness (DCCF).